Online Sexual Violence, Child Pornography or Something Else Entirely? Police Responses to Non-Consensual Intimate Image Sharing among Youth. (October 2018) - Dodge, Alexa; Spencer, Dale C.
Due to child pornography laws, non-consensual intimate image sharing among youth is subjected to complex legal landscapes in a variety of jurisdictions such as Canada, the United States, the United Kingdom, and Australia. While a growing number of scholars have problematized the use of child pornography charges to respond to these cases, there remains little understanding regarding how the police that enforce these laws conceptualize this issue and how this influences responses to these cases. Drawing from interviews with members of sex crime–related units in police service organizations from across Canada, this article examines how police conceptions of non-consensual intimate image sharing among youth correspond with and/or diverge from legal and critical understandings of this issue. While it is widely understood that online and digitally enabled forms of sexual violence pose unique challenges for police, our research fills a gap in the literature by examining how police themselves understand and respond to these challenges.